Impact of long-term care insurance on medical expenditure and utilization and the comparison between different pilot schemes: evidence from China - Yifan Yao; Shanshan Yin; Wen Chen; Changli Jia; Qiang Yao; Shanquan Chen; Junnan Jiang; Kunhe Lin; Zhengdong Zhong; Yingbei Xiong; Li Xiang (BMC Public Health)
Abstract Objective This study investigates the effect of long-term care insurance (LTCI) on medical expenditure and utilization in China and compares the effects between different pilot schemes. Methods We used four-wave data from the China Health and Retirement Longitudinal Study (CHARLS) 2011–2018, covering 19 cities piloted by national government or local governments. We applied a staggered difference-in-differences (DID) strategy to identify the effect of LTCI. Heterogeneity tests were used to identify the effects of different pilot schemes. Results We found that LTCI implementation significantly reduces inpatient expenditure, annual inpatient visits, and monthly outpatient visits by 13.4%, 0.033, and 0.072, respectively. The effects of LTCI become more pronounced in pilot cities with government subsidies in financing or higher reimbursement ceilings. Compared to pilot schemes covering UEBMI & URRBMI program, the schemes only covering UEBMI program could significantly reduce inpatient and outpatient frequency by 0.029 and 0.069. Pilot schemes with more service items had lower outpatient frequency (β = -0.146), and pilot schemes with fewer service items had lower inpatient expenditure and frequency (β = -0.226 and β = -0.049). Conclusion In general, this study found that LTCI implementation could effectively reduce the expenditure and utilization of medical services. The effects of different pilot schemes vary significantly. The results of this study further supplement the existing empirical evidence on the effect of LTCI and provide important policy implications for the future development of LTCI in China and other developing countries.